Beginnings - Sawyer, Kim Vogel (Sawyer, Kim Vogel. Summerfeld trilogy., 2007)
Beth Quinn is struggling to find a place to belong in the Old Order Mennonite Community of Sommerfeld, Kansas. When she starts a business designing stained glass windows, two men -- one a Mennonite, the other not -- begin to vie for her attention. Andrew Braun, a member of the Sommerfeld fellowship, is dedicated to family and faith. Sean McCauley, the son of a successful businessman, may only be interested in Beth's talents. Will Beth look to her heavenly Father to fill the emptiness within, or will her desperate quest for love shatter more than one heart?